Back to the Roots: Reviving Tradition in a Global Age - lasaiba, Mohammad Amin (Program Studi Pendidikan Sejarah, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pattimura, 2022)
This research explores efforts to revive local traditions amid globalization, increasingly dominating various aspects of people's lives. Globalization often hurts preserving traditions, such as the marginalization of local cultural values by modernization and the homogenization of global culture. Through the literature research method, this study analyzes various scientific sources that discuss the relationship between globalization and tradition preservation, focusing on adaptation strategies that local communities can carry out. The results show that while globalization presents significant challenges, there are opportunities to preserve and adapt traditions through education, community engagement, and the judicious use of technology. This approach allows traditions to remain relevant and contribute positively to cultural identity in a modern context. The study concludes that tradition preservation is about maintaining old practices, innovation, and adaptation to ensure local cultural values survive and thrive in globalization. The findings provide a comprehensive view of how traditions can live and thrive amid changing times.